Efektivitas Implementasi Hukum Pada Kasus Penyalahgunaan Narkotika Oleh Anak di Kota Semarang - Tarisa Febby Trenada (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
This study aims to evaluate the effectiveness of legal implementation in cases of narcotics abuse by children in Semarang City. The study employs a descriptive method with a juridical-empirical approach. The findings indicate that the enforcement of laws concerning narcotics offenses involving children has not been optimal. The primary reason is that the provisions in Article 127 of Law Number 35 of 2009 on Narcotics have not been fully applied in accordance with Article 71 of Law Number 11 of 2012 on the Juvenile Criminal Justice System. Factors influencing the effectiveness of law enforcement in narcotics abuse cases by children include legal substance, legal structure, legal culture, legal awareness, and the availability of facilities and infrastructure.